Main chain polymeric metal complexes based on linkage fluorenevinylene or phenylenevinylene with thienyl(8‐hydro xyquinoline)–cadmium (II) complexes as dye sensitizer for dye‐sensitized solar cells. Issue 6 (18th February 2013) - Jin, Xueliang; Yu, Xiaoguang; Zhang, Wei; Zhou, Jun; Tang, Guipeng; Zhong, ChaoFan
Abstract Dye‐sensitized solar cells (DSSCs) have attracted interest from chemists in recent years because of their unique advantages: low cost, simple preparation technologies, and high efficiency. Three main chain polymeric metal complexes F, P1, and P2 connected with thienyl(8‐hydroxyquinoline)–Cadmium (II) complexes have been synthesized by Heck coupling and characterized by Gel Permeation Chromatography, Fourier transform infrared, 1H NMR, thermogravimetric analysis, TGA, UV‐vis, cyclic voltammetry, photoluminescence (PL) emission spectra, and the application of dye sensitizers in DSSCs has been studied. The DSSCs exhibited good performance with a power conversion efficiency of up to 1.77%, under simulated air mass 1.5 G solar irradiation. They possess good stabilities, indicating the polymeric metal complexes are suitable for the fabrication processes of optoelectronic devices. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013